Pharmacological combination of nivolumab with dendritic cell vaccines in cancer immunotherapy: an overview - Calmeiro, João (2021)
In the last decade, immunotherapy led to a paradigm shift in the treatment of numerous malignancies. Alongside with monoclonal antibodies blocking programmed cell death receptor-1 (PD-1)/PD-L1 and cytotoxic T- lymphocyte antigen 4 (CTLA-4) immune checkpoints, cell-based approaches such as CAR-T cells and dendritic cell (DC) vaccines have strongly contributed to pushing forward this thrilling field. While initial strategies were mainly focused on monotherapeutic regimens, it is now consensual that the combination of immunotherapies tackling multiple cancer hallmarks can result in superior clinical outcomes. Here, we review in depth the pharmacological combination of DC-based vaccines that boost tumour elimination by eliciting and expanding effector immune cells, with the PD-1 inhibitor Nivolumab that allows blocking key tumour immune escape mechanisms. This combination represents an important step in cancer therapy, with a significant enhancement in patient survival in several types of tumours, paving an important way in establishing combinatorial immunotherapeutic strategies as first-line treatments.